2016
DOI: 10.1371/journal.pone.0146424
|View full text |Cite
|
Sign up to set email alerts
|

Number of Children and Telomere Length in Women: A Prospective, Longitudinal Evaluation

Abstract: Life history theory (LHT) predicts a trade-off between reproductive effort and the pace of biological aging. Energy invested in reproduction is not available for tissue maintenance, thus having more offspring is expected to lead to accelerated senescence. Studies conducted in a variety of non-human species are consistent with this LHT prediction. Here we investigate the relationship between the number of surviving children born to a woman and telomere length (TL, a marker of cellular aging) over 13 years in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 70 publications
5
56
0
Order By: Relevance
“…The following empirical observations would seem consistent with this claim: (1) perinatal and childhood adversity plays an etiological role in the programming of late-life disease, resulting in increased morbidity and reduced longevity [2,12]; (2) increased fertility coincides with reduced longevity in birds and mammals [13], as well as in primates [14], although this association has not gone unchallenged in the human case [15][16][17]. From an evolutionary life-history perspective, organisms facing risks that could reduce their chances of surviving to reproductive age should, if possible, accelerate their development and thereby increase their prospects of passing on genes to future generations before becoming unable to do so due to an early death [7,18].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The following empirical observations would seem consistent with this claim: (1) perinatal and childhood adversity plays an etiological role in the programming of late-life disease, resulting in increased morbidity and reduced longevity [2,12]; (2) increased fertility coincides with reduced longevity in birds and mammals [13], as well as in primates [14], although this association has not gone unchallenged in the human case [15][16][17]. From an evolutionary life-history perspective, organisms facing risks that could reduce their chances of surviving to reproductive age should, if possible, accelerate their development and thereby increase their prospects of passing on genes to future generations before becoming unable to do so due to an early death [7,18].…”
Section: Introductionmentioning
confidence: 77%
“…Thus, even though accelerated development may prove detrimental to health and even longevity in the longer term, such costs are regarded as ones which natural selection would discount, according to lifehistory theory, given the primacy placed on reproductive success [55,[58][59][60]. Consistent with such a life-history perspective is long-standing evidence that earlier timing of reproduction and shorter lifespans are related across taxa [61], including birds and mammals [13], as well as primates [14] and humans [62,63], although, as noted earlier, inconsistencies exist in the latter case [15][16][17]. Such data become especially noteworthy if the biological processes involved in linking reproduction and lifespan play a role in regulating developmental rate, reproduction and aging, which is exactly what we are predicting.…”
Section: Hit Twomentioning
confidence: 97%
“…There may be a protective effect from female hormones during pregnancy, or a higher level of social support in larger families. At least one study found longer LTL associated with having more children, and the authors suggested that levels of estradiol experienced during pregnancy might counter the adverse physiological effects anticipated to occur from multiple pregnancies (Barha et al, 2016). Recent research also proposes that social support may have a protective effect on LTL such that higher levels of social and spousal support are associated with longer LTL (Barger & Cribbet, 2016; Barha et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 94 women, 19 were excluded from our sample because critical demographic information was missing for 2013 (e.g., no information on parity or child mortality) [40]. These exclusions resulted in a sample size of 75 women.…”
Section: Methodsmentioning
confidence: 99%
“…Previously we showed that increased parity is associated with reduced telomere shortening in women in our study population [40]. To account for this effect of parity, we included total number of children born to a woman as a covariate in our model.…”
Section: Methodsmentioning
confidence: 99%